2022
DOI: 10.3390/diagnostics12040907
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic Effects on Cervical Cancer Diagnosis and Management: A Population-Based Study in Romania

Abstract: The Pap test plays a significant role worldwide in the early diagnosis of and high curability rates for cervical cancer. However, the coronavirus disease 2019 (COVID-19) pandemic necessitated the use of multiple drastic measures to stop the spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, limiting women’s access to essential invasive and non-invasive investigations for cervical cancer diagnosis. Therefore, we aimed to determine the impact the COVID-19 pandemic had on cancer dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
2
10
1
Order By: Relevance
“…In the current study, it was demonstrated in a retrospective fashion how the COVID-19 pandemic in Romania influenced cervical cancer diagnosis and management among cervical cancer patients in the advanced and inoperable stages of the disease. These findings corroborate most of the predictions and conjecture suggesting that many cancer cases were missed throughout the ongoing pandemic, as previously observed in the entire population of patients with cervical cancer from Romania during the pandemic [ 33 ]. Additionally, we have considered that likely many patients skipped appointments or intentionally delayed or intentionally denied treatment after having a low-stage cervical cancer diagnosis that, although curable in an early phase, became inoperable, necessitating chemotherapy, radiotherapy, or combined therapy.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, it was demonstrated in a retrospective fashion how the COVID-19 pandemic in Romania influenced cervical cancer diagnosis and management among cervical cancer patients in the advanced and inoperable stages of the disease. These findings corroborate most of the predictions and conjecture suggesting that many cancer cases were missed throughout the ongoing pandemic, as previously observed in the entire population of patients with cervical cancer from Romania during the pandemic [ 33 ]. Additionally, we have considered that likely many patients skipped appointments or intentionally delayed or intentionally denied treatment after having a low-stage cervical cancer diagnosis that, although curable in an early phase, became inoperable, necessitating chemotherapy, radiotherapy, or combined therapy.…”
Section: Discussionsupporting
confidence: 91%
“…The respiratory illness, which was subsequently called ‘Coronavirus Disease 2019’ (COVID-19), spread rapidly to neighboring states and has turned into a worldwide pandemic [ 2 , 3 ]. The condition is caused by the RNA virus “severe acute respiratory syndrome coronavirus 2” (SARS-CoV-2) and is spread mostly via respiratory droplets and intimate contact with an infected person [ 4 , 5 ]. As of April 2022, WHO has verified around 500 million cases of COVID-19 globally, with more than 6 million fatalities [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…As all the other medical specialties were in one way or another affected by the ongoing situation, the COVID-19 pandemic has influenced the urology practice as well, and the insights learned throughout the course of the pandemic should promote the development of suitable patient and pathology-related recommendations for current and future pandemics [ 7 , 8 ]. Since the first months of the COVID-19 outbreak, professional organizations have exerted great commitment to adapt to the worldwide pandemic effort in order to safeguard both doctors and patients.…”
Section: Introductionmentioning
confidence: 99%